Primary malignant melanoma of the lung in oculocutaneous albino patient - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Oculocutaneous albinism is a rare autosomal recessive disorder characterized by general depigmentation. nystagmus, photophobia, and decreased visual acuity. Malignant melanoma is extremely rare in patients with albinism. We present a 41-year-old albino mate patient. who was admitted with a suspected bronchogenic carcinoma. He underwent a pulmonary resection and the diagnosis was primary malign melanoma of the lung. The patient died of tumor recurrence in the postoperative 46th month. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: albinism; malign melanomas; lung